Crystallization of Interstitial Liquid and Latent Heat Buffering in Solidifying Gabbros: Skaergaard Intrusion, Greenland ... - Namur, Olivier; Humphreys, Madeleine C. S.; Holness, Marian B. (Oxford : Oxford Univ. Press, 2014)
New compositional profiles across plagioclase grains from the Layered Series (LS), Marginal Border Series (MBS) and Upper Border Series (UBS) of the Skaergaard intrusion are used to understand the mechanisms of cumulate rock solidification and the fate of the interstitial liquid. The data show that plagioclase crystals display three types of compositional profile over the whole intrusion, as follows. (1) Grains with normal zoning, which dominate the MBS and UBS. These are interpreted as having formed at the top of a crystal mush and then buried in the cumulate pile. Crystallization of the interstitial melt resulted in liquid differentiation and produced normally zoned rims on plagioclase cores. (2) Unzoned crystals, which dominate the upper part of the LS, also crystallized at the top of the mush and were then buried in mush with a low interstitial liquid fraction or one experiencing convective movements that kept the liquid to a constant composition. (3) Crystals with a mantle of decreasing An content ...